Web-Based Application for Filling in Animal Sample Data at the Medan Veterinary Center - Barus, Aikhel Hadinata; Mariance, UC (Cattleya Darmaya Fortuna, 2024)
Current advances in information technology have provided great benefits in the business world, be it selling goods or renting services. Information technology makes it possible to process data quickly and easily so that when presenting reports the required information can be obtained precisely and efficiently. The aim of creating this system is to overcome the problem where in the service process the service user has to go to the agency, so that the process becomes inefficient and takes time. The system design was carried out using a modeling language using UML. Meanwhile, the programming used was PHP using a MySQL database. The final result of this design produces a web-based animal sample testing information system for the Medan Veterinary Center which is expected to make it easier for internet users to provide or obtain information about the Medan Veterinary Center and the procedures carried out.